The Impact of Technology Utilization and Digital Literacy on The Satisfaction of Adopting Campus Information Systems - Sidharta, Iwan; Rahmahwati, Rahmahwati (Electronic, Business, Management and Technology Journal, 2024)
In the realm of education, digital literacy encompasses various aspects such as ensuring equitable access to technology, nurturing critical thinking abilities, cultivating information literacy, and instilling responsible digital citizenship. These endeavors aim to equip individuals with the essential skills and knowledge needed to effectively and responsibly navigate the vast realm of digital information. The research aims to explore the impact of technology utilization and digital literacy on the satisfaction of adopting campus information systems. The author employed a non-parametric approach, specifically PLS-SEM, in this study by conducting a survey among students who have utilized the campus information system. The research involved a total of 243 student respondents who participated through a Google Form. The validity and reliability testing indicated that the data collected was both valid and reliable. Subsequently, the author proceeded to analyze the data using Partial Least Squares. The statistical analysis of the data revealed significant evidence that the utilization of technology, as indicated by Performance Expectancy, Effort Expectancy, and Digital Literacy, influences users' attitudes towards the campus information system, ultimately impacting user satisfaction. The originality and value of the findings lie in their contribution to the existing body of knowledge in the field. The research sheds light on the relationship between technology utilization, digital literacy, attitudes towards the campus information system, and user satisfaction. By identifying and demonstrating the significant impact of these factors, the findings provide valuable insights for academia, practitioners, and decision-makers in enhancing technology adoption and improving user experiences in the educational context. Additionally, the research adds to the literature by utilizing a non-parametric approach and incorporating a large number of student respondents, thereby strengthening the validity and generalizability of the findings. One constraint of this research is its reliance on self-reported data, which has the potential to introduce biases and inaccuracies due to the subjective nature of respondents. Furthermore, the study solely focused on the perspectives of students who have already adopted the campus information system, potentially disregarding the viewpoints and experiences of non-users. Although the sample size of respondents was considerable, it may not fully represent the entire student population, thus limiting the generalizability of the findings. Additionally, since the research was carried out within a specific educational context, the applicability of the results to other settings or institutions may be constrained. To overcome these limitations, future studies could employ a variety of data collection methods, such as longitudinal designs, and include a more comprehensive and diverse range of participants.